Correlation between Preventive Practices Towards COVID-19 and its Knowledge Among Nursing Students (International Journal of Nursing Education, 2022)
Background: Preventive practices towards COVID-19 and its knowledge among nursing students should be considered in the planning of effective educational interventions for COVID-19 pandemic and to increase awareness about the health risks brought about by the disease.Methods: A descriptive survey with quantitative approach was conducted among 330 B.Sc. Nursing students, by convenience sampling. An online data collection was carried out by sending the questionnaires through Google forms. The instruments were; Tool I- Section A – Socio-demographic data. Section B includes the Rating scale on Preventive practices towards COVID-19. Tool II- includes the questionnaire on Knowledge on preventive practices towards COVID-19. Data analysis was performed using SPSS 22.0.Results: The study report shows that most of the 321(97%) nursing students were having good preventive practices towards COVID-19. Also, majority 310(94%) of them were having good knowledge on Preventive practices towards COVID-19. There was significant correlation between the preventive practices towards COVID-19 and its knowledge among B.Sc. Nursing students and the correlation coefficient is 0.287.Conclusion: The findings of this study have provided baseline information on the current status of preventive practices towards COVID-19 and its knowledge among B.Sc. Nursing students.
Keywords: COVID-19, Knowledge, Nursing students, Preventive practices.